The effect of an electronic exchange on prices and return volatility in the fine wine market - Marcin Czupryna; Paweł Oleksy (e-Finanse: Financial Internet Quarterly, 2018)
Fine wine has become an attractive alternative asset class in recent decades. In our study, we take the market microstructural perspective and verify how innovations in trading infrastructure affect the fine wine market. More specifically, we examine the average prices and the return volatility of fine wines traded on three different trading systems: automated electronic exchange, auctions and over-the-counter agreements (the OTC market). Our findings confirm an important role of a fully automated, cost-effective wine exchange in improving pricing efficiency and reducing market risk. This may constitute useful information for professional wine traders and institutional investors, who might consider shifting from less transparent trading systems into an automated on-book venue. This may also be a valuable indication for the future development of trading infrastructure in wine and other agricultural commodity market.
Keywords: G12; Q14; L66; 330; wine trading; wine prices; return volatility; electronic exchange; auctions